Information-Seeking Strategies Among Potato Farmers In West Java, Indonesia - Ismiati Iskak, Penny (2005)
The increase in potato demand, a devaluation of Indonesian currency in 1997, and good quality of potatoes for curry created opportunities for Indonesian potato farmers to export their product. However, the export volume of fresh potatoes continues to decrease, while the import volume of processed product increases. Due to lack of information on the desired quality attributed by the consumer, the farmers are unable to meet consumer demand. Therefore, the aim of the study is to understand information-seeking behaviour among potato farmers. The study used a survey design and structured questionnaire as a means to gather data. A total of 301 respondents were selected using stratified random sampling from 1120 members of farmers' groups in central potato production of Pangalengan, West Java, Indonesia. Data were analysed using Statistical Package for Social Science (SPSS version 11.5). Statistical analysis used in the study was descriptive statistics and Spearman rank correlation. The results revealed that market information was the type of information that the respondents needed most, followed by that on input, technologies, loans, climate, and regulations related to potato farming system. Therefore, they sought the market information more frequently than the input, technology, loan, climate, and regulation information. The findings showed that to acquire information, the respondents used interpersonal sources more frequently than electronic and print media. They perceived that interpersonal sources of information are more credible than print and electronic media. Meanwhile, the respondents made contacts with family, friends, and neighbours more frequently than progressive farmers, input traders, middle traders, extension agents, personnel of FSFISSF, agricultural researchers, and staff of village cooperative (KUD). To obtain information from the sources, the respondents used the monitoring strategy more frequently than the inquiry strategy. Conversely, they engaged most in the inquiry strategy when acquiring information from extension agents; progressive farmers; agricultural researchers; input traders; and family, friends, and neighbours.